2018
DOI: 10.4085/1062-6050-385-16
|View full text |Cite
|
Sign up to set email alerts
|

Balance- and Strength-Training Protocols to Improve Chronic Ankle Instability Deficits, Part I: Assessing Clinical Outcome Measures

Abstract: Both training protocols improved strength, balance, and functional performance. More clinicians should incorporate hop-to-stabilization exercises into their rehabilitation protocols to improve the deficits associated with CAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 44 publications
1
82
1
2
Order By: Relevance
“…Unlike the study by Hall et al (2018), which reported the improvement of static balance with therapeutic exercise, the control group in this study did not show an improvement [ 50 ]. Hall et al (2018) applied proprioceptive neuromuscular facilitation and heel raise intervention as well as TheraBand exercise, similar to this study.…”
Section: Discussioncontrasting
confidence: 76%
“…Unlike the study by Hall et al (2018), which reported the improvement of static balance with therapeutic exercise, the control group in this study did not show an improvement [ 50 ]. Hall et al (2018) applied proprioceptive neuromuscular facilitation and heel raise intervention as well as TheraBand exercise, similar to this study.…”
Section: Discussioncontrasting
confidence: 76%
“…We presented the participants' demographics and the flow diagram, inclusion and exclusion criteria, CAI status, and physical activity levels in part I of this study. 16 All participants provided written informed consent, and the research was approved by Indiana University's Institutional Review Board for the Protection of Human Subjects.…”
Section: Participantsmentioning
confidence: 99%
“…This study was part of a larger study, and the procedures for each protocol have been described in detail. 16 Each participant met with a researcher (E.A.H.) 3 times each week for 6 weeks for his or her protocol.…”
Section: Rehabilitation Proceduresmentioning
confidence: 99%
“…All selected studies were conducted in participants who met the IAC recommendations for CAI. 11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Allowing duplicate counts of intervention type resulted in 15 articles using dynamic balance training (DBT) 11,14-27 , 4 articles using strength training (ST) 11,[14][15][16] , and 4 articles using mixed type. [28][29][30][31] The mixed interventions included functional activity, range of motion (ROM), strength, balance, and neuromuscular training.…”
Section: Resultsmentioning
confidence: 99%